2019
DOI: 10.1021/acs.macromol.9b00740
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Copolymerization of o-Phthalaldehyde and Functional Aliphatic Aldehydes

Abstract: There has been a resurgence of research related to poly(phthalaldehyde) (PPHA) in the past several years because of the demonstration of long room-temperature lifetime and its low ceiling temperature facilitating the ability to rapidly depolymerize the polymer at ambient conditions. This rapid depolymerization upon triggering of PPHA mixtures makes them well suited for fabricating transient devices or stimuli-responsive materials. The copolymerization of phthalaldehyde (PHA) with other aldehydes provides a rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Based on previous work on the copolymerization of phthalaldehydes, the copolymerization of the allylated phthalaldehyde and unfunctionalized phthalaldehyde was investigated. [20,22,47] The allylated monomer was successfully incorporated in the copolymerization in a manner that allows variability in cross-linking density. It was found that a 1:1 equivalence of monomers was optimal for high incorporation rates (2.5:1 PPA:Allyl PPA) of the allylated monomer as well as the best overall yields of the statistical copolymer (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous work on the copolymerization of phthalaldehydes, the copolymerization of the allylated phthalaldehyde and unfunctionalized phthalaldehyde was investigated. [20,22,47] The allylated monomer was successfully incorporated in the copolymerization in a manner that allows variability in cross-linking density. It was found that a 1:1 equivalence of monomers was optimal for high incorporation rates (2.5:1 PPA:Allyl PPA) of the allylated monomer as well as the best overall yields of the statistical copolymer (Table S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Several polyaldehyde polymers were synthesized throughout this study to test how different variables affect residue formation after thermolysis. The polymers were synthesized via a cationic polymerization mechanism, which has been shown to produce polymers with long shelf‐life 10,11 . Table 1 shows the properties of the polymers used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The depolymerization and volatilization of phthalaldehyde copolymers were investigated to see the effect of volatile comonomers on product removal 10,22 . A propanal copolymer, p(PHA‐PA) sample P1, was compared to pPHA at the previously used thermolysis conditions, 5 min at 300°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations